Diaspora and the Non-Resident Citizenship Issue - Adhikari, Khaga Nath (NCWA Annual Journal, 2025)
Diasporas are the group of people who have left their home country for various reasons but have maintained links with their homeland and society in different ways. Diasporas have become very important these days for both developing and developed countries. They have been contributing to their countries’ socioeconomic development as well as playing important roles in investment, technology transfer, foreign affairs, and other areas. Diasporas can be categorized into different types based on the reasons for leaving their homelands. Such categories include victim diaspora, colonial diaspora, trade diaspora, labor diaspora, etc. The diasporas have evolved through various phases: from early (victim) diaspora to people who migrated to other countries in search of better opportunities. This process has helped evolve different approaches to citizenship: from the traditional bounded citizenship to transnational citizenship to the currently evolving notion of global citizenship. The Government of Nepal has upheld a policy of utilizing Non-Resident Nepalis’ knowledge, skills, technology and capital for the country’s development and has made legal arrangements to facilitate NRN’s activities. The Government of Nepal issues NRN identity cards to all interested NRNs and NRN citizenship certificates to foreign citizens of Nepali origin. Legal arrangements are yet to be made to fully implement the NRN citizenship. But a seriously thought-out policy has to be formulated and implemented to effectively benefit from the knowledge, skills, technology and capital acquired by the Nepali diaspora. Under such a background, this article aims to briefly discuss the evolution of the diaspora in general, the concept of citizenship among the diasporas, and the issue of Nepali citizenship to foreign citizens of Nepali origin.